TAFSIR MAQ?SIDI UNTUK MAQ?SID AL-SHARI‘AH - Made Saihu (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2021)
This study discusses the pattern of maq?sidi interpretation which is positioned as the foundation in creating maqasid al-Shari'ah, which means that all benefits will lead to maqasid al-Qur'an. The method used in this research is library research based on several books and journals that examine the interpretation of maqasidi and its relationship with the creation of maqasid al-syari'ah. The study shows that maqasidi interpretation is a spirit in the interpretive process that moves dynamically along with human civilization to present universal moral ideals/al-maqasid al-`?mmah. This study also shows that as a method, maqasidi interpretation, requires a reconstruction of the interpretation of the Qur'an based on maqasid as a theory. The theory of maqasid shari'ah as a knife of analysis in a procedure which is then used to understand the Qur'an, resulting in a product that focuses its study on the values ??of the maqasid verses it interprets. Through this type of interpretation, the general objective of the Shari'ah to present maslahah and prevent the destruction of the world and the hereafter, can be realized. A pattern of interpretation that places benefit to maintain human purity.